To what extent do people in malaria-endemic countries know asymptomatic malaria infections? A systematic review - Taofic Bouwe; Noudehouenou Credo Adelphe Ahissou; Kimiyo Kikuchi; Moritoshi Iwagami; Daisuke Nonaka (PLoS ONE, 2026)
Introduction Malaria is a parasitic disease caused by Plasmodium parasite and transmitted to humans by infected female Anopheles mosquito. Several studies have explored community knowledge of malaria. However, despite the remarkable proportions of asymptomatic malaria, its awareness remains relatively understudied among the affected communities. Hence, this study aimed to determine the proportion of people with knowledge of asymptomatic malaria in endemic countries and describe their perspective towards malaria control interventions. The findings from this study could contribute to developing tailored interventions in both low and high-transmission settings. Method The systematic review protocol was deposited in protocols.io and registered at PROSPERO (ID: CRD42024508104). A systematic literature review was conducted searching for peer-reviewed articles on knowledge of asymptomatic malaria published from 2010 to 2024. Three databases (PubMed (MEDLINE), Google Scholar, and Web of Science) were searched. The risk of bias in the included studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool and the Mixed Methods Appraisal Tool (MMAT). A thematic analysis and a narrative synthesis were conducted to synthesise the results. The research followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results In total, 483 articles were retrieved, and 11 relevant articles were included in the analysis. According to four studies conducted among the general public, the proportion of individuals knowledgeable of asymptomatic malaria ranged from 14.2% to 79.8%. The proportion among health personnel was 88% (one study). The qualitative studies showed varied and lacking knowledge of asymptomatic malaria among the participants, as well as refusal and reluctance to adhere to interventions targeting asymptomatic Plasmodium carriers. Conclusion This review showed a lack of knowledge of asymptomatic malaria among endemic communities and a remarkable shortage of studies on related topics. For better malaria control and to accelerate disease elimination, education on asymptomatic malaria would be necessary. Given the limited number of studies, further research on knowledge of asymptomatic malaria would be crucial in various malaria-endemic areas to provide evidence for tailored interventions.